Evaluation in Hematology and BCR-ABL Molecular Profiles in Patients with Chronic Myeloid Leukemia Undergoing Tyrosine Kinase Inhibitor Therapy - Muhammad Ihza Lisan Shidqi; Budi Santosa; Muhamad Muslim; Haitami Haitami (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Chronic myeloid leukemia (CML) is a myeloproliferative malignancy due to the formation of the BCR-ABL fusion gene in chronic myeloid leukemia. This condition causes excessive cell proliferation, resulting in an increase in the number of leukocytes. Tyrosine Kinase Inhibitor (TKI) is a first-line therapy that helps reduce the percentage of the Breakpoint Cluster Region–Abelson (BCR-ABL) fusion gene in patients with chronic myeloid leukemia. This study was conducted to determine evaluation in the hematological profiles (hemoglobin levels, leukocyte counts, platelet counts) and molecular BCR-ABL in patients with chronic myeloid leukemia before and after 12 months of tyrosine kinase inhibitors therapy. This analytic observational study was administered using a cross-sectional design to in analyzing the medical records of CML patients who underwent TKI therapy at the Sub Specialist Polyclinic of Internal Medicine Hematology Oncology Ulin Banjarmasin Indonesia Regional Hospital from March 2021-April 2022. Statistical test was performed which analysis results showed that 12-month tyrosine kinase inhibitor therapy could increase the hemoglobin levels, decrease leukocyte counts, platelet counts as well as decreasing the percentage of BCR-ABL gene fusion in patients with chronic myeloid leukemia. In conclusion, evaluation of tyrosine kinase inhibitor therapy in patients with chronic myeloid leukemia obtained significant differences in the hematological profiles and the molecular BCR-ABL. Further researchers are recommended to compare the type of tyrosine kinase inhibitor therapy between Imatinib and Nilotinib on the hematological and molecular profiles of BCR-ABL in patients with chronic myeloid leukemia with a larger sample count.